Studies on A.M. Remizov’s Creative Biography: 1926–1927. Part 2. Facts and Fables of Parisian Everyday Life - Elena R. Obatnina (Russian Academy of Sciences. A.M. Gorky Institute of World Literature, 2020)
The paper contains a description of several subjects from A.M. Remizov’s biography of 1926 –1927, non present in his autobiographical prose. Individual events that required additional verification were found in the epistolary heritage, as well as in the chronicle of the literary life abroad. Not only real, but also mythical cases from the writer’s life are the subject of research. An episode related to the meeting between Remizov and Vsevolod Meyerhold in the period from 1926 to 1930, which still had no exact time reference, is considered for the first time; the participation of K.A. Somov in the publication of the novel Vzvikhrennaya Rus’ (Swirling Russia) is discovered; the motives of Remizov's literary behavior on the pages of the émigré press are examined. The paper also presents vivid events of the writer’s creative life, who in 1927, following his other literary peers, could have celebrated the 50th anniversary of his birth and 25 years of his literary life, but the feeling of literary loneliness forced him to abandon the anniversary.